2003
DOI: 10.1093/nar/gkg801
|View full text |Cite
|
Sign up to set email alerts
|

Use of locked nucleic acid oligonucleotides to add functionality to plasmid DNA

Abstract: The available reagents for the attachment of functional moieties to plasmid DNA are limiting. Most reagents bind plasmid DNA in a non-sequence- specific manner, with undefined stoichiometry, and affect DNA charge and delivery properties or involve chemical modifications that abolish gene expression. The design and ability of oligonucleotides (ODNs) containing locked nucleic acids (LNAs) to bind supercoiled, double-stranded plasmid DNA in a sequence-specific manner are described for the first time. The main mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Other advantages of LNA include its close structural resemblance to native nucleic acids, which leads to very good solubility in physiological conditions and easy handling. In addition, owing to its charged phosphate backbone, LNA is nontoxic and can be delivered into cells using standard protocols that employ cationic lipid (28). All these properties are highly advantageous for a molecular tool for diagnostic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of LNA include its close structural resemblance to native nucleic acids, which leads to very good solubility in physiological conditions and easy handling. In addition, owing to its charged phosphate backbone, LNA is nontoxic and can be delivered into cells using standard protocols that employ cationic lipid (28). All these properties are highly advantageous for a molecular tool for diagnostic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Catchpole and colleagues demonstrated that LNAs could invade plasmid DNA and remain associated with plasmid after delivery into cells (18). Giovannageli and colleagues showed that triplex-forming LNAs could block gene expression from plasmids inside permeabilized cells and bind to genomic DNA in intact cells (19,20).…”
mentioning
confidence: 99%
“…A study on a 15-mer pyrimidine TFO/LNA provided evidence that LNA-induced triplex stabilization is associated with a slower dissociation rate constant and a less unfavorable entropic contribution compared with the non-modified TFO (9). In previous works, TFO/LNAs have been used only for in vitro assays, including plasmid functionalization (10). However, LNAmodified oligonucleotides are appealing molecules: they have been successfully used as efficient antisense agents, even in vivo (for examples, see Refs.…”
mentioning
confidence: 99%